An observation of the evolution of equilibrium stress on poly(lactic acid) and poly(lactic acid)/hydroxyapatite nanocomposites. (March 2021) - Dusunceli, Necmi
Relaxation behavior provides specific information that indicates stress development with elapsed time for the determination of material characterization and constituting of material modeling. In addition, anomalous relaxation behavior of polymeric materials enables experimental analysis of some theoretical variables in constitutive equation. Equilibrium stress is one of the most prevailing variables in material modeling and it is generally considered as unmeasurable. In this study, evolution of equilibrium stress was examined with relaxation tests of two semi crystalline polymer materials, one of which was found to reach precise equilibrium stress levels. In accordance with this purpose, extensive relaxation tests were conducted on poly(lactic acid) and poly(lactic acid)/hydroxyapatite nanocomposites specimens at a wide range of temperatures from 23 ℃ and 55 ℃, and stress levels from 1 MPa to 50 MPa for poly(lactic acid) and 51 MPa for poly(lactic acid)/hydroxyapatite nanocomposites. All the specimens were subjected tensile loading–unloading and partial retraction process. The starting points of the relaxation test were chosen on unloading segment of stress–strain curves. Evolution of stress may decay, increase or decay then increase depending on the test point on unloading curves. Relaxation behavior of poly(lactic acid) and poly(lactic acid)/hydroxyapatite nanocomposites was simulated using viscoplasticity theory based on overstress for polymeric materials. Experimental results of poly(lactic acid) and poly(lactic acid)/hydroxyapatite nanocomposites were matched with numerical results of viscoplasticity theory based on overstress for polymeric materials, and viscoplasticity theory based on overstress for polymeric material model was found to have an aptitude for predicting anomalous relaxation behavior of poly(lactic acid) and poly(lactic acid)/hydroxyapatite nanocomposites. Additionally, the effect of temperature on relaxation time was investigated with using Kohlraush–Williams–Watts time-decay function. Modeling capability of Kohlrausch–Williams–Watts model was reasonable to predict short-term simple relaxation of poly(lactic acid) and poly(lactic acid)/hydroxyapatite nanocomposites. Responses of the model showed that interaction between relaxation time and environmental temperature was related to transition from glass state to rubbery state.